--- a/src/Sequents/T.thy Sat Oct 10 19:22:05 2015 +0200
+++ b/src/Sequents/T.thy Sat Oct 10 20:51:39 2015 +0200
@@ -13,22 +13,22 @@
(* delta * == {P | <>P : delta} *)
lstar0: "|L>" and
- lstar1: "$G |L> $H ==> []P, $G |L> P, $H" and
- lstar2: "$G |L> $H ==> P, $G |L> $H" and
+ lstar1: "$G |L> $H \<Longrightarrow> []P, $G |L> P, $H" and
+ lstar2: "$G |L> $H \<Longrightarrow> P, $G |L> $H" and
rstar0: "|R>" and
- rstar1: "$G |R> $H ==> <>P, $G |R> P, $H" and
- rstar2: "$G |R> $H ==> P, $G |R> $H" and
+ rstar1: "$G |R> $H \<Longrightarrow> <>P, $G |R> P, $H" and
+ rstar2: "$G |R> $H \<Longrightarrow> P, $G |R> $H" and
(* Rules for [] and <> *)
boxR:
- "[| $E |L> $E'; $F |R> $F'; $G |R> $G';
- $E' |- $F', P, $G'|] ==> $E |- $F, []P, $G" and
- boxL: "$E, P, $F |- $G ==> $E, []P, $F |- $G" and
- diaR: "$E |- $F, P, $G ==> $E |- $F, <>P, $G" and
+ "\<lbrakk>$E |L> $E'; $F |R> $F'; $G |R> $G';
+ $E' |- $F', P, $G'\<rbrakk> \<Longrightarrow> $E |- $F, []P, $G" and
+ boxL: "$E, P, $F |- $G \<Longrightarrow> $E, []P, $F |- $G" and
+ diaR: "$E |- $F, P, $G \<Longrightarrow> $E |- $F, <>P, $G" and
diaL:
- "[| $E |L> $E'; $F |L> $F'; $G |R> $G';
- $E', P, $F'|- $G'|] ==> $E, <>P, $F |- $G"
+ "\<lbrakk>$E |L> $E'; $F |L> $F'; $G |R> $G';
+ $E', P, $F'|- $G'\<rbrakk> \<Longrightarrow> $E, <>P, $F |- $G"
ML \<open>
structure T_Prover = Modal_ProverFun
@@ -47,28 +47,28 @@
(* Theorems of system T from Hughes and Cresswell and Hailpern, LNCS 129 *)
-lemma "|- []P --> P" by T_solve
-lemma "|- [](P-->Q) --> ([]P-->[]Q)" by T_solve (* normality*)
-lemma "|- (P--<Q) --> []P --> []Q" by T_solve
-lemma "|- P --> <>P" by T_solve
+lemma "|- []P \<longrightarrow> P" by T_solve
+lemma "|- [](P \<longrightarrow> Q) \<longrightarrow> ([]P \<longrightarrow> []Q)" by T_solve (* normality*)
+lemma "|- (P --< Q) \<longrightarrow> []P \<longrightarrow> []Q" by T_solve
+lemma "|- P \<longrightarrow> <>P" by T_solve
-lemma "|- [](P & Q) <-> []P & []Q" by T_solve
-lemma "|- <>(P | Q) <-> <>P | <>Q" by T_solve
-lemma "|- [](P<->Q) <-> (P>-<Q)" by T_solve
-lemma "|- <>(P-->Q) <-> ([]P--><>Q)" by T_solve
-lemma "|- []P <-> ~<>(~P)" by T_solve
-lemma "|- [](~P) <-> ~<>P" by T_solve
-lemma "|- ~[]P <-> <>(~P)" by T_solve
-lemma "|- [][]P <-> ~<><>(~P)" by T_solve
-lemma "|- ~<>(P | Q) <-> ~<>P & ~<>Q" by T_solve
+lemma "|- [](P \<and> Q) \<longleftrightarrow> []P \<and> []Q" by T_solve
+lemma "|- <>(P \<or> Q) \<longleftrightarrow> <>P \<or> <>Q" by T_solve
+lemma "|- [](P \<longleftrightarrow> Q) \<longleftrightarrow> (P >-< Q)" by T_solve
+lemma "|- <>(P \<longrightarrow> Q) \<longleftrightarrow> ([]P \<longrightarrow> <>Q)" by T_solve
+lemma "|- []P \<longleftrightarrow> \<not> <>(\<not> P)" by T_solve
+lemma "|- [](\<not> P) \<longleftrightarrow> \<not> <>P" by T_solve
+lemma "|- \<not> []P \<longleftrightarrow> <>(\<not> P)" by T_solve
+lemma "|- [][]P \<longleftrightarrow> \<not> <><>(\<not> P)" by T_solve
+lemma "|- \<not> <>(P \<or> Q) \<longleftrightarrow> \<not> <>P \<and> \<not> <>Q" by T_solve
-lemma "|- []P | []Q --> [](P | Q)" by T_solve
-lemma "|- <>(P & Q) --> <>P & <>Q" by T_solve
-lemma "|- [](P | Q) --> []P | <>Q" by T_solve
-lemma "|- <>P & []Q --> <>(P & Q)" by T_solve
-lemma "|- [](P | Q) --> <>P | []Q" by T_solve
-lemma "|- <>(P-->(Q & R)) --> ([]P --> <>Q) & ([]P--><>R)" by T_solve
-lemma "|- (P--<Q) & (Q--<R) --> (P--<R)" by T_solve
-lemma "|- []P --> <>Q --> <>(P & Q)" by T_solve
+lemma "|- []P \<or> []Q \<longrightarrow> [](P \<or> Q)" by T_solve
+lemma "|- <>(P \<and> Q) \<longrightarrow> <>P \<and> <>Q" by T_solve
+lemma "|- [](P \<or> Q) \<longrightarrow> []P \<or> <>Q" by T_solve
+lemma "|- <>P \<and> []Q \<longrightarrow> <>(P \<and> Q)" by T_solve
+lemma "|- [](P \<or> Q) \<longrightarrow> <>P \<or> []Q" by T_solve
+lemma "|- <>(P \<longrightarrow> (Q \<and> R)) \<longrightarrow> ([]P \<longrightarrow> <>Q) \<and> ([]P \<longrightarrow> <>R)" by T_solve
+lemma "|- (P --< Q) \<and> (Q --< R ) \<longrightarrow> (P --< R)" by T_solve
+lemma "|- []P \<longrightarrow> <>Q \<longrightarrow> <>(P \<and> Q)" by T_solve
end